Association of Spousal Support and Bonding Attachment with the Psychological Condition of Postpartum Mothers at Royal Prima General Hospital, Medan, Indonesia - Juita Sari; Suhartini Suhartini (Cattleya Darmaya Fortuna, 2026)
Psychological disorders during the postpartum period constitute a significant health issue that can affect maternal well-being, infant caregiving, and overall family quality of life. Several factors are presumed to be associated with the psychological condition of postpartum mothers, including spousal support and bonding attachment between mother and infant. This study aimed to analyze the relationship between spousal support and bonding attachment with the psychological condition of postpartum mothers at Royal Prima General Hospital Medan in 2025. This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 40 postpartum mothers selected using an accidental sampling technique. Data were collected using questionnaires on spousal support, bonding attachment, and the Edinburgh Postnatal Depression Scale (EPDS) to assess the psychological condition of postpartum mothers. Data analysis was conducted using univariate and bivariate methods with the Chi-Square test at a 95% confidence level, and Odds Ratios (OR) along with 95% Confidence Intervals (95% CI) were calculated. The results showed a significant relationship between spousal support and the psychological condition of postpartum mothers (p=0.001). Mothers who received good spousal support were 11.66 times more likely to have a normal psychological condition compared to those who did not receive such support (OR=11.66; 95% CI=2.221–61.27). In addition, bonding attachment was also significantly associated with the psychological condition of postpartum mothers (p=0.001). Mothers with good bonding attachment were 116.0 times more likely to have a normal psychological condition compared to those with poor bonding attachment (OR=116.0; 95% CI=9.288–1448). This study concludes that spousal support and bonding attachment are significantly associated with the psychological condition of postpartum mothers. Therefore, the involvement of husbands in supporting mothers and the early strengthening of bonding attachment should be optimized as efforts to improve maternal mental health during the postpartum period.